Find expert answers and community insights on IDNLearn.com. Our platform provides trustworthy answers to help you make informed decisions quickly and easily.
Sagot :
Answer:
x=3, multiplicity of 2
x=-5, multiplicity of 1
Step-by-step explanation:
f(x) = (x - 3)(x - 3)(x + 5)
Rewriting
f(x) = (x - 3)^2(x + 5)
Setting equal to zero
0 = (x - 3)^2(x + 5)
Using the zero product property
(x-3)^2 = 0 x+5 = 0
x-3 = 0 x= -5
x=3 x-5
Since x-3 was squared, the multiplicity is 2
Answer:
x=3, multiplicity of 2
x=-5, multiplicity of 1
Step-by-step explanation
We appreciate your contributions to this forum. Don't forget to check back for the latest answers. Keep asking, answering, and sharing useful information. Your questions find answers at IDNLearn.com. Thanks for visiting, and come back for more accurate and reliable solutions.